The Relationship of Body Mass Index With The Risk of Diabetes Mellitus In Adolescent High School In The Malang City - Dyah Widodo; Swito Prastiwi; Kasiati Kasiati (Jurnal Keperawatan Terapan, 2021)
Diabetes mellitus is a disease caused by a hormonal disorder that affects insulin 5.7% of the total population of Indonesia, including teenagers. Is a big challenge for the health sector to do the step in anticipation of the complexity of health problems caused by diabetes mellitus in Indonesia. This study aims to analyze the relationship of body mass index with risk of diabetes mellitus in adolescent high school in the city of Malang. This research is correlational research design, sampled in this study is partly a teenage high school class in Malang, city area drawn at random sampling with a large sample of 375 respondents. Research conducted at the high school SMU Negeri 6 and SMU Negeri 9 in the city of Malang, in May-August 2021. Data collection techniques using questionnaires and measurement of body mass index. Data analysis is descriptive and analytic Spearman Rho correlation with alpha 0.05 using computer. The results showed that there is a BMI (body mass index) related to findrisk of diabetes mellitus in adolescent high school in Malang with 0,000 p-values ??<? 0.05. Recommended for teens to pay attention to awake the ideal body weight, so avoid the risk of diabetes mellitus.